Analysis of English Language Use and National Identity Awareness among Students of the English Education Study Program at Nusa Cendana University - Farel Juliant Lay Moy; Pryta Christiani Agustin; Ralph Ronald Bolla; Mariana Evi Nabuasa; Mutmainnah Abdullah; Alfret Benu; Ida Nyoman Tri Darma Putra (International Journal of Education, Information Technology, and Others, 2026)
This study investigates the patterns of English language utilization and its subsequent implications on national identity awareness among students within the English Education Study Program at Universitas Nusa Cendana. Employing a descriptive quantitative methodology, data were gathered from 11 participants via a structured questionnaire evaluating three core indicators: sociolinguistic dynamics in daily interactions, internal perceptions toward the urgency of English, and the standing of the Indonesian language within academic and national spheres. The empirical evidence reveals a multilingual tendency where students frequently blend Indonesian, English, and Kupang Malay in their informal communication. Interestingly, despite the high intensity of foreign vocabulary usage in digital spaces, their appreciation for Indonesian as a unifying national instrument remains uncompromised. The majority of respondents perceive English strictly as an academic competence rather than a marker of social prestige, maintaining a high level of confidence when utilizing standard Indonesian. Ultimately, this exploration demonstrates that international language proficiency and the preservation of national language quality can coexist simultaneously. This study underscores the critical role of civic education in fostering global competence among the youth while keeping them firmly rooted in their national identity.